2016
DOI: 10.1159/000445390
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carbohydrates and Childhood Functional Abdominal Pain

Abstract: Childhood functional gastrointestinal disorders (FGIDs) affect a large number of children throughout the world. Carbohydrates (which provide the majority of calories consumed in the Western diet) have been implicated both as culprits for the etiology of symptoms and as potential therapeutic agents (e.g., fiber) in childhood FGIDs. In this review, we detail how carbohydrate malabsorption may cause gastrointestinal symptoms (e.g., bloating) via the physiologic effects of both increased osmotic activity and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 52 publications
2
62
1
Order By: Relevance
“…These data are unique but complementary to those demonstrated in shorter studies by other groups. 2,8,14,21 The increased rates of anxiety in patients with FBD is consistent with other studies that show high rates of anxiety-related disorders in pediatric patients with FBD. 22,23 Given that 17% of children in this study experienced stress and anxiety, psychological strategies need to be used in concert with dietary interventions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These data are unique but complementary to those demonstrated in shorter studies by other groups. 2,8,14,21 The increased rates of anxiety in patients with FBD is consistent with other studies that show high rates of anxiety-related disorders in pediatric patients with FBD. 22,23 Given that 17% of children in this study experienced stress and anxiety, psychological strategies need to be used in concert with dietary interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Although the present study was retrospective, it showed the LFD to be an appropriate treatment for children with FBD in a real‐world setting. These data are unique but complementary to those demonstrated in shorter studies by other groups …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, there is ample evidence to support a diffuse inflammatory mechanism in some, but not all, patients [12,13,14]. Recent studies at the intersection of biology and behavior indicate that a patient's biological make-up also plays a role in determining whether a given behavior (e.g., consuming carbohydrates) will produce pain symptoms [15]. In sum, these findings suggest significant heterogeneity in children with CAP.…”
Section: Introductionmentioning
confidence: 97%